FRI0235 Static and Dynamic-Functional Trans-Cervical Ultrasonography of the Esophagus in Systemic Sclerosis Patients. (10th June 2014) - Santoboni, G.; Luccioli, F.; Cannarile, F.; Mirabelli, G.; Alunno, A.; Bartoloni Bocci, E.; Valentini, V.; Terenzi, R.; Biscontini, D.; Gerli, R.
Abstract : Background: Esophagus is the second internal organ to be affected in systemic sclerosis (SSc), resulting in gastro-oesophageal reflux, oesophagitis and, in more advanced stages, complete atony with megaesophagus. Trans-cervical ultrasonography (TCU) has been proposed as method to study proximal esophagus as it allows to view the five layers of the esophageal wall and permits a functional evaluation of the salivary bolus transit. Objectives: To assess structural and functional alterations of the cervical esophagus in patients with SSc using TCU. Methods: Thirty-nine patients with SSc and 39 healthy subjects underwent TCU of the esophagus (Esaote MyLab25 gold; 12 MHz linear probe) with patient in supine position with the neck extended and rotated to the right, using a posterior approach to the left thyroid gland. A functional evaluation was performed to study the transit of salivary bolus during swallowing and to detect possible salivary bolus reflux and its speed. In all subjects were recorded: age, sex, weight, height, BMI, symptoms of esophageal involvement (dysphagia, heartburn). In SSc patients were additionally recorded specific autoantibodies and videocapillaroscopic patterns, disease duration and organ involvement. Results: Thickness of the muscle layer of esophagus was significantly lower in patients than in controls (1.55±0.04 mm vs 1.73±0.05 mm, P<0.05). There was no significant difference in thickness of the entire wall. A higher frequency of salivary reflux was detected by dynamic assessment in SSc patients (84.6% vs 38.4%, P<0.01). A "high speed" pattern (qualitative assessment) of bolus salivary reflux was found in 13 out of 39 patients (33%), but in none of control subjects. Quantitative assessment showed a significant difference in the speed of salivary reflux in patients compared to controls (4.8±0.5 cm/s vs 1.67±0.2 cm/s, P<0.01). There was a significant difference in wall and muscularis thickness among patients with SSc complicated by idiopathic pulmonary arterial hypertension (iPAH) compared to those not suffering from this complication (wall: 1.95±0.07 mm vs 2.4±0.11 mm, P<0.01; muscle: 1.24±0.06 mm vs 1.62±0.05 mm, P<0.01). Conclusions: SSc patients have a significant reduction in the tunica muscularis thickness, probably related to an increase of collagen fibers in the lamina with consequent muscle atrophy. SSc patients compared to controls, have a high rate of cervical salivary reflux, likely related to altered distal esophageal peristalsis. Reduced esophageal wall and muscle layer thickness was found to be associated with the development of iPAH, confirming the already known relationship between pulmonary and esophageal involvement. According to our findings, esophagus TCU may represent a non-invasive and low-cost screening test to detect esophageal involvement in SSc. However, studies with larger series of patients and with direct comparison with instrumental methods validated for the study of esophagus in SSc, such as manometry, are needed. References: Forbes A et al. Rheum 2008;48:iii36-iii39. Zhu SY et al. J Clin Ultrasound 2004;32:163-171. Denton CP et al. Eur respir Rev 2011;20:122, 270-276. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4984